Analysis Of Factors Affecting Employees Satisfaction In PT. Wangsa Jatra Lestari - Mas'ud, Mohamed Alfitouri; , Drs. M. Farid Wajdi, M.M Ph.D; , Drs. Ahmad Mardalis, MBA (2015)
The purpose of this study are: 1) To determine there is relationship or not of working environment with satisfaction of employees; 2) To determine there is relationship or not of pay & promotion with satisfaction of employees; 3) To determine there is relationship or not of job security with satisfaction of employees; 4) To determine there is relationship or not of co-workers with satisfaction of employees; 5) To determine there is relationship or not of supervisor with satisfaction of employees; and 6) To determine there is relationship or not of level of fairness with satisfaction of employees. This research is quantitative, by taking samples at PT. Wangsa Jatra Lestari. The study population and sample as many as 181 employees were taken by 150 employees. The technique of collecting data using questionnaires. The data analysis technique used is multiple linear regression analysis. The results obtained showed that: 1) There exists a positive relationship between working environment and satisfaction of employee; 2) Pay and promotion enhances job satisfaction of employee; 3) Increased job security has a positive impact on job satisfaction of employees; 4) A positive correlation exists between relationship with co-workers & job satisfaction; 5) Supervisor's supports increase the job satisfaction of employees; and 6) Increased level of fairness has a significant impact on job satisfaction. Keywords: Working Environment, Pay & Promotion, Job Security, Relationships with Co-Workers, Relationship with Supervisor, and the Level of Fairness